ANALISIS FAKTOR ORANG TUA TERHADAP STATUS GIZI BALITA PENDEKATAN TEORI HEALTH BELIEF MODEL - Mardhiyah Hayati; I K. Sudiana; Kristiawati Kristiawati (Universitas Airlangga, 2014)
Introduction: Nutritional status is a condition of between intake and nutrient requirements in the body and helps to detect early risk of health problems, especially in children who are susceptible to nutritional problems. Results of the the Department of Health 2012 that an increase in less nutrition (3.39%) and poor nutrition (1.30%) in area Puskesmas Perak Timur Surabaya. This research explained the factors that correlation to nutritional status of children in Puskesmas Perak Timur Surabaya approach theory of Health Belief Model (HBM) in 2014.Method: Data collection was in January 2014 using a cross-sectional study design. The sample was recruited with using probability sampling consist of 113 respondents. The dependent variable is nutritional status and the independent variables in the form of HBM components are perception susceptibility, perceived seriousness, perceived benefits barriers and cues to action. Analyzed with univariate using frequency distribution and bivariate test with Spearman's Rho test with a significant level of <0.05.Result: The results showed there was correlation perceptions susceptibility and nutritional status (p = 0.011), there was correlation perception seriousness and nutritional status (p = 0.000), there was correlation perception of barriers benefits and nutritional status (p = 0.004), there was correlation cues to action and nutritonal status (0,000).Discussion: Based on the results, the HBM components can affect the parents to increase nutritional status of children so it is recommended to health workers at Puskesmas Perak Timur to give adequate information about the nutritional status of children using posters, leaflets or stickers.